The correlation between trainee gender and operative autonomy during trauma and orthopaedic training in Ireland and the UK - Rosie Mc Colgan; Fiona Boland; Gerard A. Sheridan; Grainne Colgan; Deepa Bose; Deborah M. Eastwood; David M. Dalton (Bone & Joint Open)
Aims: The aim of this study was to explore differences in operative autonomy by trainee gender during orthopaedic training in Ireland and the UK, and to explore differences in operative autonomy by trainee gender with regard to training year, case complexity, index procedures, and speciality area. Methods: This retrospective cohort study examined all operations recorded by orthopaedic trainees in Ireland and the UK between July 2012 and July 2022. The primary outcome was operative autonomy, which was defined as the trainee performing the case without the supervising trainer scrubbed. Results: A total of 3,533,223 operations were included for analysis. Overall, male trainees performed 5% more operations with autonomy than female trainees (30.5% vs 25.5%; 95% CI 4.85 to 5.09). Female trainees assisted for 3% more operations (35% vs 32%; 95% CI 2.91 to 3.17) and performed 2% more operations with a supervising trainer scrubbed (39% vs 37%; 95% CI 1.79 to 2.06). Male trainees performed more operations with autonomy than female trainees in every year of training, in each category of case complexity, for each orthopaedic speciality area, and for every index procedure except nerve decompression. When adjusting for year, training level, case complexity, speciality area, and urgency, male trainees had 145% (95% CI 2.18 to 2.76) increased odds of performing an operation with autonomy and 35% (95% CI 1.25 to 1.45) increased odds of performing an operation under trainer supervision, than assisting, compared to female trainees. Conclusion: Male trainees perform more operations with autonomy during orthopaedic training than female trainees. Female orthopaedic trainees assist for a greater proportion of cases than their male counterparts. A comprehensive review of trauma and orthopaedic training is needed to identify any additional differences in training opportunities between female and male trainees, particularly with regard to progression through training. Cite this article: Bone Jt Open 2025;6(1):62–73.